Penggunaan Setsuzokujoshi Noni, Nagara-Mo Dan Nimokakawarazu Dalam Novel Tobu Ga Gotoku Karya Ryoutarou Shiba - Eka Meriani, Ni Luh; Yuliani Giri, Ni Luh Kade; Wiriani, Ni Made (Humanis; Volume 16. No. 3. September 2016, 2016)
The research with the title “The usage of setsuzokujoshi Noni, Nagara-mo and Nimokakawarazu in Novel of Tobu ga Gotoku written by Ryoutarou Shiba” aim to research the structure and meanings of setsuzokujoshi noni, nagara-mo and nimokakawaraz u on the sentences inside the Novel of Tobu ga Gotoku written by Ryoutarou Shiba . This research using agih method. The analysis structure of setsuzokujoshi noni, nagara-mo and nimokakawarazu using syntax theory according to Verhaar (2012) with the reference opinion of Makino and Tsutsui (1989&1995), while the meaning analysis using the contextual meaning theory from Pateda (2001). The result of this research representing that from the structure aspect of setsuzokujoshi noni, nagara-mo and nimokakawarazu to be combined with the verb, adjectives and noun. The form of verb ~te-iru when combined with nagara-mo, will become ~teinagara-mo form. Beside that noni dan nimokakawarazu also can be put in front of the sentences. From the aspect of contextual meaning, setsuzokujoshi noni context has meaning of person, situation context, and mood. Setsuzokujoshi nagara-mo context  has meaning of person, mood context, place context, and situation context. While setsuzokujoshi nimokakawarazu has meaning that related with purpose context, situation context, and mood context.